1988
DOI: 10.1113/expphysiol.1988.sp003122
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Trans‐synovial Flow and Plasma Osmotic Pressure, With an Estimation of the Albumin Reflection Coefficient in the Rabbit Knee

Abstract: SUMMARYThe volume of synovial fluid in a joint correlates inversely with plasma colloid osmotic pressure (COP). The inferred influence of plasma osmotic forces on trans-synovial flow was investigated directly here, in isolated perfused hindquarters of sixteen rabbits. Flow of intra-articularly infused Krebs solution across the synovial lining of the cannulated knee was recorded at controlled intra-articular pressure (18 cmH2O). Colloid osmotic pressure in the synovial microcirculation was varied by perfusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…A monotonic relation between conductance and intra-articular pressure above -9 cmH2O has been confirmed by measurements of blood-to-joint cavity conductance, i.e. the conductance of the capillary wall and synovial lining in series (Knight & Levick, 1985;Knight, Levick & McDonald, 1988). The trans-synovial movement of fluid takes place through wide interstitium-filled spaces between the lining cells, which stem from fibroblasts and macrophages, not epi-or mesothelium.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…A monotonic relation between conductance and intra-articular pressure above -9 cmH2O has been confirmed by measurements of blood-to-joint cavity conductance, i.e. the conductance of the capillary wall and synovial lining in series (Knight & Levick, 1985;Knight, Levick & McDonald, 1988). The trans-synovial movement of fluid takes place through wide interstitium-filled spaces between the lining cells, which stem from fibroblasts and macrophages, not epi-or mesothelium.…”
mentioning
confidence: 74%
“…One cannula was connected to a Gould-Statham pressure transducer calibrated by water column, to record intra-articular pressure (PI). The other was connected to an infusion reservoir of Krebs solution (for composition see Knight et al 1988), whose height above the joint controlled P. An intervening drop counter recorded flow into the joint, and trans-synovial flow (Q.) was calculated as measured inflow in the steady state after 15-20 min at constant pressure minus the wall's residual rate of viscous creep (Levick, 1979).…”
Section: Intra-articular Pressure and Trans-synovial Flow Measurementmentioning
confidence: 99%
“…Fenestrated vesicles, transcellular gaps (Neal & Michel, 1997), or unfenestrated, vesiculo-vacuolar organelles (Feng et al 1997) have also been reported. The quantitative sieving properties of these ultrastructural changes during VEGF perfusion are unknown, but the reflection coefficient to albumin of fenestrated capillaries is 0·78 in both the knee joint (Knight et al 1988) and the ascending vasa recta (Pallone, 1992), and the sieving properties of fenestrated endothelium of the glomerulus remain intact with a high reflection coefficient to albumin (Savin et al 1992). These previously published findings are therefore consistent with the results described here.…”
Section: Discussionmentioning
confidence: 99%
“…where d V/dPj is the mean compliance of the rabbit synovial cavity at that pressure (Knight & Levick, 1982 Knight, Levick & McDonald, 1988). Five concentrations were investigated (10, 22-5, 55, 110, 150 g l-) and five to six animals were studied at each concentration.…”
Section: Methods In Vitromentioning
confidence: 99%